2016
DOI: 10.1002/ejoc.201600262
|View full text |Cite
|
Sign up to set email alerts
|

Chemoenzymatic Synthesis of Chiral 1‐Benzyl‐5‐(hydroxymethyl)‐2‐piperidone Enabled by Lipase AK‐Mediated Desymmetrization of Prochiral 1,3‐Diol and Its Diacetate

Abstract: General rightsThis document is made available in accordance with publisher policies. Please cite only the published version using the reference above. Full terms of use are available: http://www.bristol.ac.uk/pure/about/ebr-terms FULL PAPER Abstract:The synthesis of (R)-1-benzyl-5-(hydroxymethyl)-2-piperidone 1 from key synthon monoacetate (R)-3 has been accomplished conveniently in 6 steps with 93% ee and in 44% overall yield. The key step involved lipase AK desymmetrization of diol 4 to produce monoacetate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 37 publications
0
16
0
Order By: Relevance
“…Lipase AK was also established to be best for the hydrolysis of diacetate 53. [97] Due to the obvious advantages of immobilisation of enzymes as mentioned in section 3, lipase AK will be immobilised on three different nanomaterials -Fe3O4 magnetic nanoparticles, [106] covalent triazinepiperazine linked polymer (CTPP-1) [107] and silica nanospheres (KCC-1) [108] to identify the most suitable support material. The optimum conditions for immobilisation of lipase AK on these nanomaterials will be tested by varying the method of immobilisation, temperature, pH of buffer used for immobilisation, concentration of cross-linking agent, etc.…”
Section: Research Methodologiesmentioning
confidence: 99%
See 4 more Smart Citations
“…Lipase AK was also established to be best for the hydrolysis of diacetate 53. [97] Due to the obvious advantages of immobilisation of enzymes as mentioned in section 3, lipase AK will be immobilised on three different nanomaterials -Fe3O4 magnetic nanoparticles, [106] covalent triazinepiperazine linked polymer (CTPP-1) [107] and silica nanospheres (KCC-1) [108] to identify the most suitable support material. The optimum conditions for immobilisation of lipase AK on these nanomaterials will be tested by varying the method of immobilisation, temperature, pH of buffer used for immobilisation, concentration of cross-linking agent, etc.…”
Section: Research Methodologiesmentioning
confidence: 99%
“…We have developed a chemo-enzymatic approach for the synthesis of chiral piperidone 39 (Scheme 17) using tert-butyl acrylate 47, and dimethyl malonate 48 as the starting material. [97] The key step in this synthetic route is the enzymatic desymmetrisation of diol 52 and diacetate 53. Using only lipase AK, we have demonstrated that both enantiomeric products (R)-54 and (S)-54 monoacetates can be prepared effectively with 93% ee.…”
Section: Scheme 13: Enzymatic Resolution Of Racemic Ester Rac-87 To (mentioning
confidence: 99%
See 3 more Smart Citations